The effect of cooling on brewer's yeast quality - Nkosi, John C (Department of Chemical Engineering, 2023)
The primary concern of a brewer is to produce beer of a desired flavour and quality, in an economic and efficient manner. In large scale brewing operations, process efficiency and beer quality rely on consistent fermentation. Stewart (1977) reports that improper handling of yeast in the brewing process may result in beer of sub-standard quality.